Pengaruh Pendekatan Auditory, Intellectually and Repetition (AIR) terhadap Kemampuan Pemecahan Masalah dengan Bentuk Soal Cerita - Engla Wetri; Rahmi Putri; Ria Deswita; Aan Putra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The purpose of this study was to investigate the effect of Auditory, Intellectually, and Repetition (AIR) approach through students mathematical problem solving ability with mathematical word problems.This study used quantitative approach with experiment method. The research design was posttest-only control group. The population was all of eighth grade students in MTsN 2 Kota Sungai Penuh. Two samples were choosen with draw. Conventional method was implemented in control group, while AIR approach was implemented in experiment group. The instrument in this study was students mathematical problem solving ability with story questions test that the test items was analyzed first. The instrument was given in the end oflearning process in both groups. The result of the data analysis was obtained that there was an effect of AIR approach through students mathematical problem solving ability with mathematical word problems.